TEMPERATURE STRESSES IN HARDENING UNINTERRUPTEDLY-CASTED INGOT AT CONTROLLED COOLING - Ju. S. Postolnik; V. I. Timoshpolskij; I. A. Trusova; P. E. Ratnikov (Литьë и металлургия)
Analytical method is developed and calculations of temperature and thermostressed state at hardening of continuously-casted slab slugs at high-level cooling are carried out on the basis of the equivalent sources method.